Screening for group B Streptococcus (GBS) at labour onset using PCR: accuracy and potential impact – a pilot study. (2nd January 2018) - Ramesh Babu, Sandhya; McDermott, Rachel; Farooq, Irum; Le Blanc, David; Ferguson, Wendy; McCallion, Naomi; Drew, Richard; Eogan, Maeve
Abstract: This pilot study assessed the diagnostic accuracy and potential impact of a rapid PCR-based screening test for the detection of group B Streptococcus (GBS) at the onset of labour for the purpose of optimising intrapartum antibiotic prophylaxis (IAP). Vaginal and rectal swabs from a convenience sample of 158 women were analysed by conventional broth-enriched culture and a rapid PCR test. Overall, GBS carriage was 18.98% by culture and 19.62% by PCR. PCR for the detection of GBS had a sensitivity of 93.1%, specificity of 96.67% and area under the curve (AUC) of 0.95. Only 19.3% GBS-positive women received IAP. Three-fourths of babies born to GBS-positive mothers did not receive surveillance for early-onset GBS disease. Of the women who received IAP, only 32.5% were GBS carriers. Seventy-four percent of the GBS-positive mothers delivered more than 5 h after recruitment, which gives adequate swab to delivery interval for appropriate antibiotic prophylaxis in labour. Impact statement: What is already known about this subject: Appropriate intra-partum treatment of colonized mothers reduces the risk of GBS transmission to neonates. Universal ante partum screening of pregnant women or IAP based on risk factors in labour for GBS prevention fail to accurately identify and treat the woman who actually harbors GBS in the birth canal in labour. A PCR based rapid test, allows for real-time assessment of GBS carriage in labour. What this study adds: This study highlights the fact that a large number of GBS carriers in labour, who could potentially infect their babies, do not receive IAP, and most of their babies do not receive added surveillance in the neonatal period for EOGBS disease. It also confirms that PCR testing at onset of labour is a highly sensitive and reliable test that identifies the women who are GBS carriers in labour and hence need IAP. What the implications are of these findings for clinical practice and/or further research: Timely provision of IAP for the appropriate woman is possible by adopting universal GBS screening at the onset of labor using GBS-PCR. This would involve additional costs to health care facilities and added work to laboratory personnel.